Instrumental Variables and Causal Mechanisms: Unpacking the Effect of Trade on Workers and Voters - Robert Gold; Christian Dippel; Stephan Heblich; Rodrigo Pinto (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We identify how German voters responded to the labor market turmoil caused by increasing trade with low-wage manufacturing countries. We first establish that import competition increased voters' support for only extreme (right) parties. We then decompose this populist `total effect' of trade on voting into a `mediated effect' running through labor market adjustments and an independent `direct effect'. Our Causal Mediation Analysis reveals that direct and indirect effect work in opposite directions.
Keywords: C36; D72; F16; 330